2024
DOI: 10.1039/d3ta06651g
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the unknown with AI: multiobjective Bayesian optimization of non-noble acidic OER catalysts

Ken J. Jenewein,
Luca Torresi,
Navid Haghmoradi
et al.

Abstract: Experimental catalyst optimization is plagued by slow and laborious efforts. Finding innovative materials is key to advancing research areas for sustainable energy conversion, such as electrocatalysis. Artificial intelligence (AI)-guided optimization...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…These droplet cells find significant application in electrocatalysis, where they facilitate the scanning of various solid electrocatalysts with diverse chemical compositions. [49,50] These electrocatalysts are typically prepared using a custom-programmed pipetting robot [49,50] or, alternatively, through a physical vapor deposition process. [51] Scanning droplet setups are also employed in corrosion research.…”
Section: Experiments Automation and Standardizationmentioning
confidence: 99%
“…These droplet cells find significant application in electrocatalysis, where they facilitate the scanning of various solid electrocatalysts with diverse chemical compositions. [49,50] These electrocatalysts are typically prepared using a custom-programmed pipetting robot [49,50] or, alternatively, through a physical vapor deposition process. [51] Scanning droplet setups are also employed in corrosion research.…”
Section: Experiments Automation and Standardizationmentioning
confidence: 99%
“…As catalyst behavior also depends on the temperature, a temperature-controlled flow field could improve the cell design. The conventional SFC can be used for automated high-throughput approaches, , so an adaption to the S-GDE’s flow field to analyze multiple catalysts would be beneficial for accelerating catalyst layer testing aimed at high-throughput analysis.…”
Section: Conclusion and Outlookmentioning
confidence: 99%
“…The Cantor alloy electrocatalyst surfaces completely lose OER activity after prolonged cycling (∼2000 CV cycles), exhibiting pseudocapacitor characteristics (Figure 1a), which was also observed for MnTiO x for the acidic OER. 39 Previous studies on extraordinarily stable HEA electrocatalysts 8,27,34 typically measure the changes in overpotentials or perform chronoamperometry or chronopotentiometry measurements to examine stability. In our study, we observed that the decrease in the level of the OER activity in the Cantor alloy is relatively slow compared to that of unary metals, for example, Co. 17 The increase in overpotential of the Cantor alloy microelectrode from ∼360 to ∼380 mV took about 3.5 h of the OER cycling (∼500 cycles, Figure 1b).…”
Section: Dissolution Measurements Of the Cantor Alloy During The Oermentioning
confidence: 99%